Konektivitas Jawa-Bugis melalui Jalur Rempah Nusantara: Studi Komparasi Primbon Jawa dan Kutika Bugis - Widyaningrum, Rahmatia Ayu; Dwiadmojo, Ghis Nggar (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This research aims to compare the text contained in the Palintangan Palindhon Pakedutan Primbon Manuscript (Add 12311) in the collection of the British Library, which is in Javanese language, with the Kutika Ugi' Sakke Rupa (PRI/15/MMK/KKT 1530) in the collection of the Mulawarman Museum, East Kalimantan, which is in Bugis language. Both manuscripts contain text containing information on the quality of the days of the month. Both texts have the characteristics of primbon, namely a Javanese literary genre that contains various knowledge. Even though the Bugis people do not know the word primbon, the closeness of the Kutika Ugi' Sakke Rupa text to the Primbon Palintangan Palindhon Pakedutan shows that there is a connection between the two cultures that has been going on for a long time. Before the term primbon was known by Javanese people, namely during the Kawi era, the cross-culture was one of the impacts of trade activities on the spice route. Through the spice route, the two cultures are connected. The similarities and differences found in the two texts reinforce that the relationship between Javanese and Bugis is not only diplomatic but can also be found through material culture. This connection also explains that the similarities between the two are a monogenesis phenomenon.